The legality of the intervention in Mali - Saldarriaga Velásquez, Giuliana Stephanie (2014)
Due to the crisis lived in Mali since 2012, due to a non-international armed conflict between the government and different armed groups, the Security Council of the United Nations Organization declared that the situation in Mali constituted a threat to international peace and security. This led to the military intervention in Mali by France. This article aims to analyse the arguments with which the French government attempted to justify its intervention in order to determine if those arguments are legal or not.